Methyl orange dye removal by dimethylamine functionalized graphene oxide - Sew, Hui Juen; Noor Nazihah Bahrudin,; Nur Amilah Fadlina Basri,; Mohd Haniff Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Graphene oxide (GO) functionalized with dimethylamine (DMA) was successfully prepared using a facile technique. GO was first synthesized using the modified Hummers method, followed by chemical functionalization with DMA in the presence of an electrophilic linker, i.e., epichlorohydrin (ECH). FTIR analysis of the end product ascertains the successful synthesis of GO as well as its functionalization with DMA. Typical characteristic peaks attributed to GO and DMA are clearly discernible in the spectrum. The effect of pH, adsorbent dosage, dye concentration, and contact time towards methyl orange (MO) dye removal was studied and reported herein. In summary, enhanced adsorption of methyl orange was observed for DMA functionalized GO compared to GO alone. 90% removal was observed with 10 mg/L of MO concentration, pH = 2 at temperature 25 °C and 5 mg of adsorbent. Modelling study shows that the pseudo-second-order kinetic model and Freundlich isotherm model provide better fitness to the experimental data.